Global governance, development and human security : the challenge of poverty and inequality - Thomas, Caroline (Pluto Press LondonGB, 2000)
Looks at the human security challenge and examines global development practice in the 1980s and 1990s. Focuses on development pathways for human security in the twenty-first century.